Book Reviews & Ph.D notices - Kvistad, Erika; Henriksen, Line; Bülow, Morten Hillgaard (Kvinder, Køn & Forskning, 2017)
Book Reviews: Adam Golub and Heather Richardson Hayton (eds.): "Monsters in the Classroom: Essays on Teaching What Scares Us" (reviewed by Erika Kvistad). Mark Fisher: "The Wierd and the Eerie" (reviewed by Line Henriksen). Donna Haraway: "Staying With the Trouble Making Kin in the Chthulucene" (reviewed by Morten Hillgaard Bülow). Ph.D. notices: Kristian Møller: "The mediatization of intimacy. A study of hook-up apps and gay men's intimacy cultures" Marie-Louise Holm: "Fleshing out the self: Reimagining intersexed and trans embodied lives through (auto-)biographical accounts of the past"